Characteristics of chitosan fiber and their effects towards improvement of antibacterial activity. (15th March 2022) - Li, Jianhui; Fu, Jimin; Tian, Xiao; Hua, Tao; Poon, Tszyin; Koo, Mingkin; Chan, Wingming
Abstract: We selected eight kinds of chitosan fibers to characterize and analyze their composition, surface morphology, and mechanical properties. Crucially, we investigated their antibacterial activity against Escherichia coli, Staphylococcus aureus and Candida albicans and the dependence on the molecular weight (Mw) and the degree of deacetylation (DD). On that basis, the relationship between antibacterial activity and Mw and DD can be established. Finally, the antibacterial mechanism of chitosan fiber was obtained. The results show that the inhibition rate of samples I, K, L, and M against Staphylococcus aureus first increased and then decreased with the increase of Mw, and their bactericidal activity against Escherichia coli decreased with the increase of Mw when the DD was similar. This study provides an effective strategy for characterizing the chitosan fiber and the resultant relationship between antibacterial property and structural parameters that may benefit the enhancement of antibacterial activity and application in antibacterial textiles. Graphical abstract: This study provides an effective strategy for characterizing the chitosan fiber and the resultant relationship between antibacterial property and structural parameters that may benefit both the improvement of antibacterial activity and enhancement of application in antibacterial textiles. Unlabelled Image